1994
DOI: 10.1002/jmv.1890420207
|View full text |Cite
|
Sign up to set email alerts
|

Etiological role of hepatitis E virus in sporadic fulminant hepatitis

Abstract: Non-A, non-B hepatitis viruses have been implicated as the etiological agent(s) in up to 60% of patients with fulminant hepatitis. These agents are reported to induce a higher mortality than other causes of fulminant hepatitis. Hepatitis E virus (HEV) and hepatitis C virus (HCV) at present constitute the major identifiable non-A, non-B hepatitis agents. Of these, HEV has been established as the sole cause of epidemic hepatitis in Afro-Asian countries, and fulminant hepatitis has been recorded during such epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 32 publications
3
68
0
3
Order By: Relevance
“…16 HEV is predominantly transmitted through contaminated water and food. [1][2][3][4][5][6][7]14,15,[17][18][19][20][21] The disproportionate pregnancy rate among the women and girls with ALF in the current study may raise the suspicion of sexual transmission of HEV. However, sexual transmission of HEV has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 HEV is predominantly transmitted through contaminated water and food. [1][2][3][4][5][6][7]14,15,[17][18][19][20][21] The disproportionate pregnancy rate among the women and girls with ALF in the current study may raise the suspicion of sexual transmission of HEV. However, sexual transmission of HEV has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…40 HEV as a cause of ALF has not been reported from the west, whereas it is the commonest cause of ALF in the current study as well as earlier reported studies from India. [3][4][5][6][7]11,12,14,15 At our center, liver transplant facilities are not available; therefore, the mortality rate of 57% documented in the current study would indicate the true frequency of death attributable to ALF. In the US multicenter study, 25% to 29% of patients with ALF were subjected to liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the benign course of illness caused by this agent, with case fatality rates of around 0.1%-0.4% 1,14 Hepatitis E is the most common cause of ALF in endemic regions of the world, with high mortality (25%) in pregnant women ( Figure 3). [23][24][25][26] Hepatitis B has a case fatality of around 1.0% and constitutes a significant percent of ALF in various endemic regions of the world. 1,13 Chronic hepatitis B can cause ALF during reactivation, especially after immunosuppression therapy.…”
Section: Viral Hepatitismentioning
confidence: 99%
“…7 Hepatitis C is a very rare cause of ALF in Europe and the United States, 27,28 although a number of series from Japan and India have found evidence of hepatitis C in the non-A, non-B group of patients. 24,25,29 The etiology of ALF is unknown in 30%-50% of patients and is presumed to be caused by yet unidentified non-A-E viral agent. This non-A-E agent accounts for 90% of patients with late onset hepatic failure, and identification of this agent is a matter of great priority.…”
Section: Viral Hepatitismentioning
confidence: 99%